Security Threats and Privacy Issues in Vehicular Ad-Hoc Network (VANET): Survey and Perspective - Ajulo, Emmanuel Bamidele; Akinyede, Raphael Olufemi; Adewale, Olumide Sunday (Journal of Information, 2018)
In Vehicular Ad Hoc Networks (VANETs) Wireless-equipped vehicles are able to communicate with each other as well as Road-Side Units (RSUs) located at strategic places on the road, this enables the formation of self-organized networks connecting the vehicles and RSUs. The (vehicles) nodes are fast mobile causing the network topology to change frequently and unpredictably. Since VANETs do not really rely on any form of central administration or control, nodes in the wireless range dynamically discover each other and establish connection with each other. Due to the pervasive nature of the mobile nodes, it cannot be assumed that VANETs will always be under the control of their owners; nodes could be stolen or tampered with. Each vehicle (node) acts as an independent router and fault detection and network management becomes distributed and more difficult. The shared wireless medium is accessible to both legitimate and illegitimate users; and this has raise formidable research challenges to providing security for this network. This paper take a selective review of the published research work carried out in the security and privacy issue of VANET between 2003 and 2015 and derived a new perspective into the security and privacy attacks in VANET.